Incidental DTPA and DMSA uptake during renal scanning in unknown bone metastases - Balci, Tansel Ansal; Ciftci, Ismail; Karaoglu, Aziz (Japanese Society Nuclear Medicine, 2006)
We report a patient with DTPA and DMSA uptake on unsuspected bone metastases. He had severe pain due to grade 3 hydronephrosis of his left kidney. When Tc-99m DTPA and DMSA renal scanning were performed for preoperative evaluation, abnormal radiopharmaceutical uptake on the iliac area was noted. Pancreatic adenocarcinoma metastases to bone were subsequently defined. This patient is a very demonstrative case in respect of having all DTPA, DMSA and HDP uptakes in bone metastases. The type of the tumor has to be added to the list of extrarenal uptake of DTPA and DMSA as a rare cause.
Keywords: DTPA; DMSA; extrarenal uptake; incidental visualization